How to access and exploit natural resources sustainably: petroleum biotechnology. Issue 5 (3rd August 2017) - Sherry, Angela; Andrade, Luiza; Velenturf, Anne; Christgen, Beate; Gray, Neil D.; Head, Ian M.
Summary: As we transition from fossil fuel reliance to a new energy future, innovative microbial biotechnologies may offer new routes to maximize recovery from conventional and unconventional energy assets; as well as contributing to reduced emission pathways and new technologies for carbon capture and utilization. Here we discuss the role of microbiology in petroleum biotechnologies in relation to addressing UN Sustainable Development Goal 12 (ensure sustainable consumption and production patterns), with a focus on microbially‐mediated energy recovery from unconventionals (heavy oil to methane), shale gas and fracking, bioelectrochemical systems for the production of electricity from fossil fuel resources, and innovations in synthetic biology. Furthermore, using wastes to support a more sustainable approach to fossil fuel extraction processes is considered as we undertake the move towards a more circular global economy. Abstract : How to access and exploit natural resources sustainably: petroleum biotechnology.